Active Immunization Against cVIP and It`s Role on the Pattern of Sequence Length and Pause Days in Domestic Hen (Gallous domesticus) - Reddy, I.J.; David, C.G.; Raju, S.S. (International Journal of Poultry Science, 2006)
Chicken vasoactive intestinal peptide (cVIP) is a hypothalamic PRL (PRL) releasing factor in birds and it plays an important role avian reproduction. Our objective was to determine whether active immunization against cVIP would increase the sequence length, decrease intersequence pause days, and there by improving egg production in White Leghorn (WLH) by decreasing the prolactin (PRL) concentration during the active period of productive cycle in birds. WLH birds at 13 weeks of age were divided into two experimental groups consisting of 21 birds in control and immunized birds. At 17th week of age, 21 birds were immunized with synthetic chicken VIP (conjugated with keyhole limpet haemocyanin KLH-cVIP), followed by three booster doses at four weekly intervals with a total of four immunizations. Controls were given placebo in place of immunogen. cVIP antibody titers were consistent till the age of 72 weeks in immunized birds. Active immunization of the birds against cVIP significantly (P< 0.01) decreased the circulating PRL during and after the withdrawal of immunizations and PRL levels were found to decrease up to the age of 72 weeks of age, resulting in significantly lower incidence of shorter sequences, with significantly (P< 0.01) lower number of intersequence pause days, egg laying sequence lengths in birds immunized against cVIP. Total number of pause days were significantly reduced in immunized birds compared to controls. Egg production increased by 7.00% in the immunized birds over the control birds with the available resources under normal husbandry practices. It is observed that the laying pauses are mainly due to fluctuations in the concentration of PRL above physiological levels in circulation and keeping the PRL hormone under check will influence egg production, pause days, sequence length, persistency in egg production with almost an egg a day. It is conclude that the physiological pauses that occur during ovulatory sequences can be disrupted effectively using active immunization against cVIP, which modulates PRL levels, that may interfere with the follicular recruitment and subsequent oviposition thereby improving egg production in white leghorn hens.